Quantum Griffiths phase inside the ferromagnetic phase of Ni1-xVx - Wang, R; Gebretsadik, A; Ubaid-Kassis, S; Schroeder, A; Vojta, T; Baker, P; Pratt, F; Blundell, S; Lancaster, T; Franke, I; Möller, J; Page, K (American Physical Society, 2017)
We study by means of bulk and local probes the d-metal alloy Ni1−xVx close to the quantum critical concentration, xc≈11.6%, where the ferromagnetic transition temperature vanishes. The magnetization-field curve in the ferromagnetic phase takes an anomalous power-law form with a nonuniversal exponent that is strongly x dependent and mirrors the behavior in the paramagnetic phase. Muon spin rotation experiments demonstrate inhomogeneous magnetic order and indicate the presence of dynamic fluctuating magnetic clusters. These results provide strong evidence for a quantum Griffiths phase on the ferromagnetic side of the quantum phase transition.